Horta vertical com sistema de monitoramento IoT - Novaes, Matheus Sinto [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
With the increasing demographic growth and consequente food necessities, urges the need to find efficient methods for producing food. Hydroponic systems are efficient alternatives to plantations and the verticalization is a nice solution to produce more in less space. So this kind of system can work, it's important to keep track of some data. This essay propose a vertical hydroponic system with telemetry to an indoor garden, where the data are exposed through an API and persisted in a database. The measured data are regarding water and ambient parameters: pH, electroconductivity, temperature, illumination and water level, enabling its analysis. The system counts with artificial illumination and water pump that can be activated through the API.

Com o crescente aumento demográfico e consequente necessidade alimentar, deve-se procurar métodos eficientes de se produzir comida. Sistemas hidropônicos são alternativas mais eficientes para plantações e a verticalização é uma solução para produzir mais em menos espaço. Para este tipo de sistema funcionar é importante acompanhar alguns parâmetros. Este trabalho propõe um sistema de horta vertical hidropônica com telemetria, onde os dados são expostos através de uma API e persistidos num banco de dados. Os dados medidos são referentes a variáveis da água e do ambiente, que são pH, eletrocondutividade, temperatura, iluminação e nível; possibilitando assim sua análise. O sistema conta com iluminação artificial e motor, que podem ser ativados pela API.
Vertical garden with IoT monitoring system
Keywords: Internet of Things; Vertical garden; Telemetry; Internet das Coisas; Horta vertical; Telemetria; API